Teaching leadership in undergraduate nursing programs in Portuguese-speaking countries: a documentary study - Vitória Talya dos Santos Sousa; Jocilene da Silva Paiva; Maria Rayssa do Nascimento Nogueira; Ana Caroline Rocha de Melo Leite; Edmara Chaves Costa; Thiago Moura de Araújo; Patrícia Freire de Vasconcelos (Revista de Enfermagem da UFPI)
Objective: To analyze the presence of clourses on the subject of "leadership" in the curricula of Nursing programs at Higher Education Institutions in Portuguese-speaking countries. Methods: A qualitative, documentary study, with data collected from official sources of educational institutions, focusing on Nursing programs in 10 Portuguese-speaking countries. The curricular matrices of the programs were analyzed and data on the classes were extracted and organized into figures and tables. Results: 155 institutions were identified, 75 of which offer a Nursing degree. When considering the institutions that offer a Nursing degree, 18 have courses that include the topic "leadership" in their syllabus, and they are only located in three countries: Brazil, Portugal, and Macao.  Conclusion: There are still gaps in the training of nurses in Portuguese-speaking countries, which is a cause for concern given the struggle for Nursing to be recognized and valued in Portuguese-speaking countries.